Influence of workers performance to implementation of security, safety, health, and sustainability - Arya Putra N.N, Sidiq; Widyaningsih, Nunung; P.K. Bintoro, Bambang (International Journal of Engineering and Technology, 2020)
This study was carried out to investigate and analyze the effect of worker behavior on security, safety, health, and sustainability (In Indonesian referred to as Keamanan, Keselamatan, Kesehatan, and Keberlanjutan or K4). This study employed a descriptive research method using a quantitative approach. The sample/ subject of the study was obtained through a random sample method with a total sample of 55 respondents. Data analysis in this study was conducted using Partial Least Square (PLS); a variant based choice method of the Structural Equation Modeling (SEM) method. This method was used to explain the relationship of an independent variable with its indicators and to illustrate the relationship between an independent and dependent variable using the SmartPLS software. The results of the analysis indicate that K4 was strongly influenced by the behavior of construction workers with the highest significance value in the sequence, namely the workers, attitude, knowledge, and actions.